Imaginaires médiatiques de la résilience pastorale en Afrique subsaharienne - Étienne Damome; Nadège Soubiale (Communiquer)
Media often reflect the dominant ideologies of a given era, especially when they are carried by public institutions. The study presented in this article deals with one of the major contemporary paradigms of public development aid, based on the concept of resilience. As an example, we chose the pastoral farming sector in West Africa, which since the 2000s has been the focus of major aid agencies. In the field of analysis of media content in ICS, this example provides an illustration of the manner in which the contents of the public and private press of West African countries reflect the contents of the sponsors’ speeches, which refer very explicitly to this paradigm.